Foot and Ankle Injury Surveillance of Collegiate Student-Athletes Utilizing the Pac-12 Health Analytics Program. Issue 1 (January 2022) - Ross, Lexie; Hamati, Mary C.; Tuffiash, Michael; Robell, Kevin; Hunt, Kenneth J.
Category: Ankle; Sports; Other Introduction/Purpose: In order to monitor student-athlete health, identify risk factors associated with sports injuries, and develop and evaluate injury prevention programs at the collegiate level, it is necessary to implement and utilize high quality sports injury surveillance systems. The Pac-12 Health Analytics Program (HAP) addresses this need by standardizing electronic medical record entries and common data elements across all Pac-12 institutions. The literature suggests that collegiate student-athletes are at higher risk for certain injuries that have chronic effects on their health-related quality of life. Previous investigations utilizing the HAP database found ankle injuries to be the second most prevalent lower extremity injury in this population. This study aims to build upon these previous findings and further characterize below-knee injuries using the HAP database. Methods: We retrospectively reviewed archival data from Pac-12 student-athletes followed in the HAP database, a deidentified Pac-12 conference-wide sports injury surveillance system used to study the epidemiological characteristics of varsity student- athletes from 2017-2020. Data collection is part of the standard of care provided by varsity athletic trainers and entered into the Presagia Sports electronic medical record. This data is then deidentified and automatically sent to the Pac-12 for inclusion in the HAP. Individual authorization forms were obtained from student-athlete participants prior to deidentification and inclusion in the HAP database. Student-athletes who sustained a lower extremity (LE) injury below the knee were included. Data on demographics and injury characteristics were analyzed. Results: Foot and ankle injuries account for 20.3% (6, 776/33, 432) of all database injuries, representing 23.4% (2, 214/9, 444) of all student-athletes. Female-athletes (26.8%) had a higher injury rate than male-athletes (20.9%) (p<0.00001). Lower leg injuries were categorized as ankle (43.1%), foot (25.3%), lower leg (18.4%), and ankle/heel (13.2%). Ligament sprain was the most common injury type (38.1%) followed by tendinopathy (14.4%) and inflammation (7.9%). Males were more likely to sustain an acute injury (81.8%) than females (63.7%). Injuries most commonly occurred on synthetic (46.0%). Common mechanisms of injury (MOI) included running (21.6%), contact with another player (18.4%), and contact with a hard object (14.8%). Injuries most commonly occurred during in-season (48.9%) compared to off-season (25.5%) and pre-season (20.9%) segments of the competitive year. Half of injuries (50.0%) resulted in lost time from sport, however only 6.7% of injuries were season ending and only 2 injuries (<0.01%) resulted in medical retirement. Conclusion: Most ankle injuries occurred on synthetic surfaces, suggesting an opportunity for enhanced monitoring and prehabililitation programs for sports that utilize these types of surfaces. Further investigations accounting for covariates and risk factors may inform injury prevention strategies and improve student-athlete wellness. While the Pac-12 HAP database is early in development, this report demonstrates the potential value that injury surveillance systems can provide for student-athlete health. The Pac-12 HAP is a collaborative and effective injury database, setting the standard for other regional conferences.